Micropaleontology and biostratigraphy efficient tools in archaeological research. Raw material provenance in the upper Palaeolithic Kasthtsa cave, loannina region (Greece) - Zambetakis-Lekkas, A.; Elefanti, P. (Bulletin of the Geological Society of Greece, 2007)
The present paper discusses the contribution of Micropaleontology and Biostratigraphy to the archaeological research using as a case study the Upper Palaeolithic cave of Kastritsa in the Ioannina basin, north-west Greece. Thin section analysis applied to a selected number of stone tools from the site suggested that raw materials employed in their manufacture could originate from the Ioannina basin or even from outcrops in the proximity of the cave. This suggest that once Palaeolithic groups arrived at the cave, they practised low mobility which in turn suggests that a range of subsistence opportunities were available in the area allowing to its inhabitants extensive stays. This hypothesis is well supported by the archaeological record of the site. Micropaleontology and Biostratigraphy can be a useful method in the investigation of raw material provenance, especially when sedimentary rocks are studied, and it can provide significant insights into huntergatherer mobility strategies.